Globalization: the Challenge of Building Awareness of Bela Negara Among the Young Generation - Dartono, Dartono; Santoso, Budi (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
Threats to the existence of the state are increasingly complex, but youth awareness of Bela Negara tends to be reactive and stagnate on the orientation of physical threats. The role of family, school, and community as pillars of education is indicated to work by itself. This literature study aims to explain awareness, the influence of dominant factors, and alternative strategies for youth awareness of Bela Negara in the Era of Globalization. Through the application of descriptive-qualitative method the study concludes; (1) The threat to the existence of an increasingly complex state has not been responded to by the understanding of the younger generation in a comprehensive manner. (2) The presence of non-physical threats that are also destructive, such as the understanding of the counter value of Pancasila and local wisdom, the flood of imported products, etc. feels so natural, that most young people don't realize it, (3) Contextualization of understanding through education is the most important element, and material for understanding the counter values ​​of Pancasila and local wisdom, the threat of imported products, etc. as a threat to the existence of the state, it becomes a priority for insertion in education, both in the family, school, and community spheres. The existence of relevant measures and policies is also very much needed to continuously improve the effectiveness of their implementation.